Optimal Key Handover Management for Enhancing Security in Mobile Network - Suma, V.; Haoxiang, Wang (Journal of Trends in Computer Science and Smart Technology, 2021)
The 3GPP long term Evolution or System Architecture Evolution (LTE/SAE) was designed for the dispositioning of the mobile networks towards 4G. The significant hurdle of 4G is about cementing the privacy and security gap. Due to the disclosures in the connectivity of public networks, a single malicious device could jeopardize the operation of a whole network of devices. The key deliverance handling within the 3GPP LTE/SAE is developed to unauthorize the keys that are being attacked and, in result, to alienate the miscreant keys off the chain of network. The proposed article recognizes the attacks that jeopardize the safe connectivity among the stops in the network chain and details the vulnerability of the key deliverance administration to desynchronization attacks. Even though the periodic upgrade of the root could prove to be a fundamental part of the system, the work proposed brings an emphasis on reducing the impact of desynchronization attacks which currently are unable to be prevented efficiently. The main focus of the design is to shed light on the ways the network operators work to confirm the optimal intervals for the periodic updates to reduce the signal weightage while providing secure user mobility. The analysis and model simulations intend to disclose the influence of the period of root key upgrade on integral operational levels such as constellation and user experience.